2023
DOI: 10.3390/ijerph20032579
|View full text |Cite
|
Sign up to set email alerts
|

Soluble ST2 as a New Oxidative Stress and Inflammation Marker in Metabolic Syndrome

Abstract: Background: Metabolic syndrome (MS) is a complex and prevalent disorder. Oxidative stress and inflammation might contribute to the progression of MS. Soluble ST2 (sST2) is an attractive and druggable molecule that sits at the interface between inflammation, oxidative stress and fibrosis. This study aims to analyze the relationship among sST2, oxidative stress, inflammation and echocardiographic parameters in MS patients. Methods: Fifty-eight patients with MS were recruited and underwent physical, laboratory an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 65 publications
(70 reference statements)
0
2
0
1
Order By: Relevance
“…The sST2-related inflammatory cell recruitment may trigger oxidative stress, as demonstrated by the positive association with hydrogen peroxide. In the study by Zhang in HF patients, sST2 levels positively correlated with serum malondialdehyde, while they negatively correlated with the antioxidant superoxide dismutase activity, suggesting a role for elevated sST2 in enhanced redox status [74,75]. Matilla et al [76], using proteomics and immunodetection approaches, demonstrated that sST2 downregulated mitofusin-1 (MFN-1), a protein involved in mitochondrial fusion, in human cardiac fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sST2-related inflammatory cell recruitment may trigger oxidative stress, as demonstrated by the positive association with hydrogen peroxide. In the study by Zhang in HF patients, sST2 levels positively correlated with serum malondialdehyde, while they negatively correlated with the antioxidant superoxide dismutase activity, suggesting a role for elevated sST2 in enhanced redox status [74,75]. Matilla et al [76], using proteomics and immunodetection approaches, demonstrated that sST2 downregulated mitofusin-1 (MFN-1), a protein involved in mitochondrial fusion, in human cardiac fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…Roy et al [74] reported that, among patients with metabolic syndrome, increased levels of circulating sST2 correlated positively with inflammatory markers: IL-6, osteopontin, ICAM-1, myeloperoxidase and a classical reactive oxygen species marker nitrotyrosine (NT-Tyr). Furthermore, the investigators demonstrated a correlation between oxidative stress markers like 8-hydroxy-2 ′ -deoxyguanosine (8-OHdG) and levels of hydrogen peroxide.…”
Section: Discussionmentioning
confidence: 99%
“…La implementación de paneles de biomarcadores junto con criterios de diagnóstico tradicionales puede mejorar la precisión diagnóstica y permitir un enfoque más personalizado en la prevención y manejo del síndrome metabólico. Sin embargo, se necesitan más estudios y validaciones en poblaciones diversas antes de su implementación clínica rutinaria (Roy et al, 2023).…”
Section: Conclusionesunclassified